(untitled) (Plant Bulletin, 2025)
Mosquito-borne diseases, particularly those transmitted by Aedes aegypti, pose significant global health risks. Chemical repellents such as DEET are widely used; however, concerns regarding toxicity and environmental safety have increased interest in natural alternatives. Essential oils, with diverse bioactive properties, represent a promising option, though their repellent efficacy depends on the type and proportion of active compounds. This study employed Response Surface Methodology (RSM) to optimize the proportions of neem, lemongrass, sesame, and mint oils for developing an effective plant-based repellent. A total of 27 formulations were prepared and tested against A. aegypti. Analysis of Variance (ANOVA) confirmed the statistical significance of the model, demonstrating that repellent activity was strongly influenced by essential oil composition. The optimized formulation consisted of 37.931 parts neem oil, 69.338 parts lemongrass oil, and 2.828 parts sesame oil, with no mint oil. This combination achieved a predicted effectiveness score of 51.548 and a desirability index of 1.00, indicating high performance and stability. Results highlighted neem and lemongrass oils as the primary contributors to repellency, while sesame oil enhanced formulation stability. Overall, the study successfully optimized an essential oil-based repellent, offering a safe, natural, and sustainable alternative to synthetic chemicals with potential for further development and commercialization.